Pengaruh Jaminan Sosial Terhadap Produktivitas Karyawan Pada PT Barokah Suralaya - mahfudoh (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
Social Security is used to encourage employees to improve the quality and quantity of their work. Employee social security is expected to have an impact on work productivity, so that in turn it will lead to the achievement of the desired commitment. The formulation of the problem in this study are How is Social Security given to employees of PT. Barokah Suralaya? How Employee Productivity at PT. Barokah Suralaya? What is the Effect of Social Security on Employee Productivity at PT. Barokah Suralaya? The research method used in this research is survey method and this research is associative. The population of this study were 30 employees of PT. Barokah Suralaya and taken a sample of 30 people or the entire population (sample of respondents) in accordance with Sugiyono’s opinion. The results showed that: first the test results for the social security questionnaire analysis at PT. Barokah Suralaya, out of 30 respondents stated social security at PT. Barokah Suralaya can be said to be good with the acquisition of 1323: 1500 = 0.882 or 88.2 or 88%. Second, the test results for employee productivity questionnaire analysis at PT. Barokah Suralaya, out of 30 respondents can be said to be good with the acquisition of a value of 1299: 1500 which is 0.866 or 86%. Third based on the calculation of the correlation coefficient found r = 0.769 is between 0.60 - 0.799 which means the level of relationship is strong, to test the significance by using t test, based on calculations obtained t count = 6.363> t table 2.048 in this case the error rate is 5%. And the results of the calculation of the mineralized coefficient test (Cd) obtained results = 59.13% social security related to employee productivity, while the remaining 40.87% was influenced by other factors not examined by the author.